Intelligence Interconnection in The Democratic Transition in Indonesia - Reza Ilham Maulana; Sapto Hermawan; Asianto Nugroho (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Democracy has faced various challenges over thousands of years, particularly concerning transitions that depend on social and political factors. The role of intelligence in democratic transitions is crucial but can be used to maintain power undemocratically. In Indonesia, post-reform, democracy has not been fully consolidated. The repressiveness of law enforcement and legal bias towards political elites are major factors in the decline of democracy. This research employs a normative legal research method with a prescriptive nature, aiming to analyze the intelligence's involvement in the democratic transition process in Indonesia. The research approach encompasses analytical, historical, comparative, and philosophical dimensions. Primary legal materials such as legislation regulations are utilized as data sources, alongside secondary legal materials like books and journals. Data collection techniques utilize the PRISMA method, and data analysis is conducted deductively using the same method. The findings of this research indicate that the cycle of democratic transition influences both the democratic system and intelligence activities. Subsequently, a case study in Indonesia examines complex intelligence issues, attributable to regime changes and inconsistent political policies. Hence, a comparative study with Brazil, which is institutionally more complex and structured, is deemed necessary.